Altruisme dalam Relasi Dakwah Kaum Sayyid dan Kyai di Rembang Jawa Tengah - Ahmad Hidayatullah (Fakultas Dakwah dan Ilmu Komunikasi, 2024)
The sayyid and kyai in muslim sosio-religi context in Java indeed often experience ups and downs in their relationships. But today, in fact, the average sayyid is in a more dominant position, at least as a religious spiritual leader. This is because in the belief of the majority of Muslims - not to mention the kyai- indeed positioned sayyid as a descendant of the Prophet who should have received respect and appreciation. This of course cannot be generalized, but mostly what happens in the field is like this. It's different from what happened in the Rembang area, where the sayyid actually provide more space for the kyai to stand in front of leading the ummat. This research use qualitative with a phenomenological-historical approach, the researcher tries to explore how altruism in the relationship between sayyid and kyai in Rembang. The results of this study can be concluded that Alturism that occurs in the sayyid-kyai relationship has actually started since the Walisongo era (Sunan Bonang to be precise) as the manifest of Al-Muhadjir I, the period of Sayyid Abdurrahman (Mbah Sambu) as the manifest of Al-Muhadjir II, until the current era of the Alawiyin era as the embodiment of Al-Muhadjir III. A harmony that can be used as a prototype in national and religious life.